MODERN APPROACHES TO MEDICAL IMAGE PROCESSING USING COMPUTER VISION BASED ON ARTIFICIAL INTELLIGENCE - Allashkurov Dilshodbek Mansurovich; Abdullayev Abdulla Fayzulla ugli; Jumanazarov Javlon Shohnazar ugli; Muminbek Khayrullayev (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article explores modern approaches to medical image processing based on artificial intelligence (AI) and computer vision technologies. It analyzes the importance of acquiring, analyzing, enhancing, segmenting, and using images from MRI, CT, X-ray, and ultrasound scans for real-time clinical decision-making. The study also examines the role and potential of deep learning, convolutional neural networks (CNNs), and transfer learning in medical diagnostics.